Comparison of self-assessed physical activity profiles across socio economic status of adults in Brgy. Matandang Balara, Quezon City - Cabral, Carmen Luisa P. 2000-; Sabado, Marvin Luis C.
Physical activity (PA) is recommended for the prevention and rehabilitation of chronic diseases and adverse health conditions. PA level can be measured in total PA and in four domains: PA done at work, during transport, at home, and during leisure time. This study compared the PA profiles across socioeconomic status (SES) of 60 adults (18-59 y/o) residing in Brgy. Matandang Balara, using a household status questionnaire and the IPAQ-LF. Kruskal-Wallis tests determined differences, if any, across SES in Occupational PA, Transport PA, Household PA, Leisure-time PA, and Total PA. Significant differences were found between the Low-Middle SES groups in OPA, HPA, and Total PA, as well as between the Low-High SES groups in OPA. All other comparisons were found to have non-significant differences. For further study, it is recommended to include a larger sample size or area, collect more information in surveying, or employ other instruments in measuring PA